2011
DOI: 10.1007/s11947-011-0652-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microwave Heating on Sensory Characteristics of Kiwifruit Puree

Abstract: Abstract:The effect of microwave processing on the characteristics of kiwifruit puree

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 33 publications
3
14
0
Order By: Relevance
“…The values obtained are similar to those presented by Montefiori et al (2005) and Benlloch-Tinoco et al (2012). After processing, parameter a* presented positive values slightly higher than 0 while H* decreased.…”
Section: Influence Of Kiwifruit In Syrup Processing On Physicochemicasupporting
confidence: 87%
“…The values obtained are similar to those presented by Montefiori et al (2005) and Benlloch-Tinoco et al (2012). After processing, parameter a* presented positive values slightly higher than 0 while H* decreased.…”
Section: Influence Of Kiwifruit In Syrup Processing On Physicochemicasupporting
confidence: 87%
“…(,b) observed that the microwave‐treated kiwi puree had a higher L* value than the control, while the conventional thermal heated sample had a lower L* value after processing, which is different from this study. The increase in L * values of the two differently treated samples may be connected with the degradation of pigments in kiwi puree at high temperature (Benlloch‐Tinoco et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…In general, fruit products have characteristic flavor and taste which attract the consumer. In case of a crushed product like puree, the consistency or viscous nature is one of the most important criteria for their acceptance (Benlloch‐Tinoco and others ). Both the facts are reflected by the ranking of the quality attributes assessed during the sensory evaluation of the pineapple puree.…”
Section: Resultsmentioning
confidence: 99%
“…There are several methodologies using either trained people or consumers that quantitatively evaluate the sensory properties. For the sensory evaluation by a trained panel test, fuzzy reasoning is the most reproducible and standard approach applied for several food products (Jaya and Das ; Sinija and Mishra ; Benlloch‐Tinoco and others ). In fuzzy mathematical approach, the fuzzy sets of panel ratings for individual sensory attributes are transformed or defuzzified into membership functions and decision variables thus avoiding the halo‐effect at the time of ranking (Lee and Kwon ).…”
Section: Introductionmentioning
confidence: 99%